Interim results on concession agreements for the city of Perm and the Perm region - E. V. Rozhkov (Вестник университета)
The article focuses on the ongoing economic processes associated with the conclusion of concession agreements in Perm and the Perm Territory. It is noted that two dozen such agreements have been concluded over the past year. Based on the study of information on concessions in Perm, it is shown that not all agreements are beneficial. The article notes the analysis relevance of concluded agreements. Despite the fact that all agreements are closely monitored by various structures, the economic or social effect does not always manifest. The work is based on the theoretical method of research. Several agreements concluded in 2022 have been analyzed and evaluated and the effect of which can be expected in 25–30 years. Replacement of electric transport in Perm is necessary, but not at the payment expense of the municipality residents. The article analyzes the expenditure part of the Perm budget and the expenditure part of the budget of the Perm Territory for 2023 as part of payment under concession agreements. Based on the generalization of the data obtained, the article draws conclusions that can be taken into account by local governments.